A Review of Existing and Emerging Treatment Interventions for Alzheimer's Disease - Saleem, Muskaan; Sohail, Myra; Akhtar, Ahmad (International Clinical Neuroscience Journal, 2025)
Cognitive decline and progressive neuropathy due to Alzheimer's disease (AD) are on the rise throughout the world today. By impairing function and reducing the affected person's quality of life, it worsens the global burden of the disease. Many treatment options are available; however, it is important to note that each has its pros and cons and should be compared side by side to develop an individualized therapeutic approach. While a few new advanced therapeutic discoveries gain traction, such as the use of polyethylene glycol (PEG)-modified black phosphorus nanosheets (BP-PEG) and revolutionary gene editing using CRISPR/Cas9, there is a need for more data available from clinical trials for a better understanding of the new techniques being worked on. Some advancements, although promising, have yet to progress from animal models to human clinical trials. A call for further investigation appears to be necessary to weigh the advantages and disadvantages of both pharmacological and non-pharmacological therapy for AD.